Coping with emotions in professional lives: Novice teachers’ voices in Indonesian secondary schools - Jeane Theresia Limeranto; Paulus Kuswandono (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2023)
Novice teachers often encountered some challenges in their professional work that might influence their emotions. It is quite reasonable that some EFL novice teachers may still struggle to manage their negative emotions to cope with classroom problems. Some emotions could be freely expressed positively, whereas other emotions were left unexpressed for some reasons. This study aimed to answer two research questions, namely: (1) what kinds of emotions do novice teachers frequently experience in teaching? (2) How do novice EFL teachers cope with their emotions in professional life? This study employed a qualitative method and carried out semi-structured interviews to gain in-depth data from the participants' perspectives in dealing with their emotions. The instruments employed were interview-guidelines questions and open-ended questions. The result of the present study revealed that, first, all novice teachers frequently experienced two main challenges in teaching, namely students’ misbehaviours and disrespectful behaviours. These challenges could influence teachers' emotions of anger, being overwhelmed, and worries. Second, the findings demonstrated that teachers employed three strategies, namely self-regulation, self-talk, and a problem-focused strategy to manage and handle their emotions in teaching. In addition, the present study suggested beneficial implications, limitations, and directions for further research. Keywords: Emotions, EFL Novice Teachers, and Strategies